Śrīvyāsayogimañjūṣā: (Śrīvyāsatīrthaśrīmaccaraṇastotrasaṅgrahātmikā) - Mādhvācārya, Em. (Dvaitavedāntadhyayanasaṃśodhanapratiṣṭhānam, 2023)
Collection of stotras, poems, Kannada songa in praise of Vyāsatīrtha, 1460-1539, Madhva religious leader